2017
DOI: 10.3126/jist.v22i1.17767
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF CuO-NANOADDITIVE BLENDED ENGINE OIL

Abstract: Copper oxide (CuO) nanoadditives were successfully synthesized in laboratory by precipitation technique. X-ray diffraction spectroscopy (XRD) showed the crystalline nature of CuO with the average crystal size of 10 nm. The prepared CuO has been blended with engine oil. Thus prepared modified engine oil showed good kinematic viscosity 158 cSt and 19.06 cSt at 40 ⁰ C and 100 ⁰ C respectively. The viscosity index was also found to be improved to 122. Similarly, the pour point was also found to be considerably dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…After treated used lubricating oil (UO) samples, changes in the specific gravity values were observed as shown in Figure (3).…”
Section: Specific Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…After treated used lubricating oil (UO) samples, changes in the specific gravity values were observed as shown in Figure (3).…”
Section: Specific Gravitymentioning
confidence: 99%
“…Depending on what was obtained from the experimental results, it was noticed that the specific gravity of the used lubricating oil (UO) has increased compared to the new and base oil. The specific gravity of the used oil was (0.892, 0.907) g/cm 3 for gasoline, and diesel engine respectively. It can be said that the reasons behind these results are that the increase in the number of aromatic compounds in the oil results in an increase the specific gravity, while an increase the saturated compounds results in a decrease in the specific gravity also the used lubricating oil contained solids materials, which led to a high density [28].…”
Section: Specific Gravitymentioning
confidence: 99%
“…Lubricant Oil Physicochemical Testing F Te Navada et al [37] CuO + pongamia oil  Kumar et al [38] CuO + sunflower oil  Gupta et al [39] CuO + 5W30 engine oil  Subedi et al [40] CuO + 20W50 engine oil the flash temperatures were identified at a concentration of 1.1061 wt%, a speed of 217.6768 rpm, and a load of 5.0909 N. Baskar et al [32] investigated the tribological performance of journal bearings using SAE20W40 synthetic lubricant and chemically modified rapeseed oil (CMRO) as a bio lubricant, both dispersed with CuO, WS2, and TiO2 nanoparticles as anti-wear additives. The journal-bearing test rig was used to assess the COF, wear rates, and oil film thickness at a load of 10 kN l and a speed of 3000 rpm.…”
Section: Reference Lubricant Oil Synthesis Compositionmentioning
confidence: 99%
“…In present study, CuO has been used to degrade dye from aqueous solution. A number of methods that have been adopted to synthesize CuO nanoparticles such as sol-gel 6 , precipitation 7 , solid state reaction 8 , sono-chemical 9 , microwave irradiation [10][11][12] , plasma 12 and thermal decomposition 13 . Among them, simple Author for Correspondence: A. Rajbhandari (Nyachhyon), Central Department of Chemistry, Tribhuvan University, Kirtipur, Kathmandu, Nepal.…”
Section: Introductionmentioning
confidence: 99%